Mechanical, structural and dissolution properties of heat treated thin-film phosphate based glasses - Stuart, Bryan W.; Gimeno-Fabra, Miquel; Segal, Joel; Ahmed, Ifty; Grant, David M. (Elsevier, 2017)
Here we show the deposition of 2.7 μm thick phosphate based glass films produced by magnetron sputtering, followed by post heat treatments at 500 °C. Variations in degradation properties pre and post heat treatment were attributed to the formation of Hematite crystals within a glass matrix, iron oxidation and the depletion of hydrophilic P-O-P bonds within the surface layer. As deposited and heat treated coatings showed interfacial tensile adhesion in excess of 73.6 MPa; which surpassed ISO and FDA requirements for HA coatings. Scratch testing of coatings on polished substrates revealed brittle failure mechanisms, amplified due to heat treatment and interfacial failure occurring from 2.3 to 5.0 N. Coatings that were deposited onto sandblasted substrates to mimic commercial implant surfaces, did not suffer from tensile cracking or trackside delamination showing substantial interfacial improvements to between 8.6 and 11.3 N. An exponential dissolution rate was observed from 0 to 2 h for as deposited coatings, which was eliminated via heat treatment. From 2 to 24 h ion release rates ordered P > Na > Mg > Ca > Fe whilst all coatings exhibited linear degradation rates, which reduced by factors of 2.4–3.0 following heat treatments.